Sum rate analysis of two‐unicast wireless energy harvesting system. Issue 7 (25th March 2019) - Liu, Yingting; Ding, Haiyang; Pan, Zhengwei; Yang, Hongwu; Yan, Chunman
Abstract : The authors study the sum rate of a two‐unicast wireless energy harvesting system. The system consists of two source nodes, two destination nodes and one energy constrained relay node, which only harvests energy from the signals transmitted by the source nodes for its operation. Each source node transmits the signal to its corresponding destination node via the help of the relay node. The transmission process is divided into two time slots each with the same time duration. In the first time slot, two source nodes transmit the signals to the relay node and the destination nodes, and the relay node uses the power splitting (PS) protocol for harvesting energy. In the second time slot, adopting analogue network coding, the relay node retransmits the mixed signal to the destination nodes using the harvested energy. Considering network coding noise, the analytical expressions of a near optimal adaptive PS factor that leads to a maximal sum rate is derived. Numerical results corroborate the analytical results and show the superior performance of the proposed scheme in comparison with the conventional one.